Building Information Modeling 2015
DOI: 10.1061/9780784413982.ch06
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Green BIM Process Model (IGBPM) for BIM Execution Planning in Green Building Projects

Abstract: The symbiotic convergence of green building and building information modeling (BIM) is represented by an emerging trend -green BIM. Project teams find that synergies between green and BIM can improve project outcomes and they are in a better position to accomplish established sustainability goals. Nevertheless, the full potential of green BIM is yet to be explored, as indicated by recent market research. The hypothesis is that for companies to successfully deliver green BIM project, a holistic approach that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Green BIM methods are being adopted by more businesses as both BIM and green construction are gaining popularity. This is a new development in the architectural, engineering, and construction sector that employs BIM for the transmission of "green building" projects and aims to gain from collaborations between the two [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green BIM methods are being adopted by more businesses as both BIM and green construction are gaining popularity. This is a new development in the architectural, engineering, and construction sector that employs BIM for the transmission of "green building" projects and aims to gain from collaborations between the two [1].…”
Section: Introductionmentioning
confidence: 99%
“…Stakeholders in the sector can evaluate the display of green buildings with the aid of analysis techniques. "Building information modelling (BIM)" gives designers, designers, and developers the ability to evaluate the display of green buildings at the preconstruction phase [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Family is a parametric component which includes other parameters of free regulation that controls metafile's material, size, location and other information [25]. Other than that, family is the basis and essence of Revit software, the more the parameter means the more the information we can obtain and the more the embody value of BIM technology [26]. There are five basic commands namely stretching, integration, rotation, lofting and lofting integration that can create all sorts of family files.…”
Section: Family Library Constructionmentioning
confidence: 99%
“…Currently, a considerable amount of research has been done in the area of integration of BIM and sustainability in construction. Project teams have found that synergies between green building and BIM can help to improve the accomplishment of sustainability goals [14]. This interdisciplinary synergy is well known with the name of "green BIM" or "6D BIM".…”
Section: Integrating Building Information Modeling and Sustainable Buildings Designmentioning
confidence: 99%
“…Similarly, some of the most developed software for performing LCA in buildings are SimaPro®, GaBi®, Tally®, Athena Impact Estimator®, and NIST BEES®. Researchers have pointed out that a unique software package does not exist that can provide all the needed functions at all the stages for a sustainability assessment for buildings [10], [14]. Yet, through interoperability and data exchange between applications it is possible to develop integrated green BIM tools.…”
Section: Integrating Building Information Modeling and Sustainable Buildings Designmentioning
confidence: 99%